A Technological Innovation Drip Irrigation for Dry Land Chile Farming in Rural Salut, Kayangan Sub-District, North Lombok Regency, West Nusa Tenggara, Indonesia: Technological Innovation Drip Irrigation for Dry Land Chile Farming in Rural Salut, Kayangan Sub-District, North Lombok Regency, West Nusa Tenggara, Indonesia - Halil, Halil (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
The high cost of manual irrigation in dry land vegetable farming is a serious problem in dry land farming which is always faced by farming households every year. Therefore, innovation in drip irrigation technology with an automatic gravity control system using plastic waste is very necessary for irrigation of dray land vegetables farms. This research aims to analyze and find the level of savings in irrigation water use, cost efficiency and profitability of drip irrigation technology. It was a the short to medium-term Action research method starting at the beginning of the dry season. The research approach applied is participatory action research, namely action research by applying a rural community participatory approach. The results showed that innovative drip irrigation technology was able to save water and casual labors. Drip irrigation technology is very profitable, financially and economically feasible to develop in dry land vegetable farming. However, there is concern that there is a tendency for this technology to be difficult to implement in rural areas of Rural Salut because of the relatively expensive materials and equipment for drip irrigation. Therefore, irrigation equipment can be adjusted or adapted to overcome the high cost by replacing some components with cheaper and more readily available materials. The water requirement for chili cultivation in one growing season is around 22,000 liters per 500 m2 at the cost of IDR 150,000. Meanwhile, by manual method (surface flow), namely by draining water from drilled wells to the planting area of ??75,000 liters per 500 m2 with a monastery of IDR 400,000. It proves that the drip irrigation technology can save water and energy consumption. The chili farming calculations show that the financial turnover obtained from chili cultivation using drip irrigation technology was IDR 5,525,000 per 500 M2, while that obtained by local farmers was IDR 3,365,000.00 per 500 M2.